Simulasi Pemilihan Partai Politik Menggunakan Simple Additive Weighting - Edy Prayitno; Marsono Marsono; Dedi Rahman Habibie; Ita Mariami; Asyahri Hadi Nasyuha (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Problems in political party elections involve a number of issues which include corruption and political scandals which can damage public trust, campaign promises which are often not kept, elections which are too personal which obscure more important political issues, high polarization and an imbalance between ruling and opposition parties, election manipulation and election crimes, problems related to campaign financing that can affect the independence and integrity of political parties, limited access to information that can influence voters, lack of diversity representation within political parties, media polarization that makes constructive dialogue difficult , as well as limitations in electoral systems that can affect the representation and responsiveness of political parties. The use of the SAW method can be applied using criteria found in actual conditions so that the party election simulation in this research can be used as an insight into the conditions in political party elections. This provides insight to the wider community on how to choose a good and careful party. This research shows that Political Party A is the best among several other political parties which are used as alternatives with a calculation result of 0.9675 using Simple Additive Weighting